2019
DOI: 10.31234/osf.io/qdp98
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Idiographic Approach to Personality Development: Examining Change and Consistency in Self-Concept

Abstract: The field of personality development almost exclusively relies on nomothetic measures (i.e., measures that are designed to capture universal, shared characteristics). Over-reliance on nomothetic measures can neglect important, individualized aspects of personality that are not captured with standard nomothetic measures. The current study takes an individual, idiographic approach to studying personality development by examining the development of one's selfconcept. Participants (N = 507) provided 20 answers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…With the exception of studies of ipsative change that test the consistency of profiles of personality traits within a person over time (e.g., Block, 1971; De Fruyt et al, 2006; Roberts, Caspi, & Moffitt, 2001; Roberts et al, 2006), few studies take an individual, idiographic approach to personality development where the assessment of personality is based on within-person associations (although see Jackson, Lord, Strube, & Harms, 2018). Idiographic techniques (where the sample size is one person or N = 1) refer to methods used for measuring and modeling individuals where the individual is considered truly only relative to him or herself—that is, where personality is defined as the ordering of variables within a person rather than the ordering of people across a single trait dimension.…”
mentioning
confidence: 99%
“…With the exception of studies of ipsative change that test the consistency of profiles of personality traits within a person over time (e.g., Block, 1971; De Fruyt et al, 2006; Roberts, Caspi, & Moffitt, 2001; Roberts et al, 2006), few studies take an individual, idiographic approach to personality development where the assessment of personality is based on within-person associations (although see Jackson, Lord, Strube, & Harms, 2018). Idiographic techniques (where the sample size is one person or N = 1) refer to methods used for measuring and modeling individuals where the individual is considered truly only relative to him or herself—that is, where personality is defined as the ordering of variables within a person rather than the ordering of people across a single trait dimension.…”
mentioning
confidence: 99%
“…Investigations that have done so have revealed that individuals do reach for unique descriptors for themselves and that these show consistency over time (e.g. Jackson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, idiographic assessment does not require or assume that individuals will share in which phenomena capture their experiences. Investigations that have done so have revealed that individuals do reach for unique descriptors for themselves and that these show consistency over time (e.g., Jackson, Lord, Strube & Harms, 2019).…”
Section: Modeling Idiographic Coherencementioning
confidence: 99%
“…Recently, there have been calls for an idiographic approach to change, where a person's personality is assessed and modeled relative to only him or herself (Beck & Jackson, 2020ab;Cabrieto, Tuerlinckx, Kuppens, Hunyadi, & Ceulemans, 2018;Jackson, Lord, Strube & Harms, 2019;Wright et al, 2019). In regard to studying personality change, an idiographic approach alleviates concerns over how well broad, nomothetic models of personality capture individuallevel personality structure.…”
mentioning
confidence: 99%